Arabica coffee–macadamia intercropping: A suitable macadamia cultivar to allow mechanization practices and maximize profitability - Perdoná, Marcos J.; Soratto, Rogério P. [UNESP] (Wiley, 2016)
Intercropping Arabica coffee (Coffea arabica L.) with trees species that generate an economic return, such as macadamia (Macadamia integrifolia Maiden & Betche), has been suggested as an alternative for diversifying and maximizing income. However, there is no information on how macadamia cultivars affect the performance of coffee plants, system mechanization, and profitability. An 8-yr experiment was conducted in southeastern Brazil, to evaluate the growth, yield, and profitability of Arabica coffee intercropped with six macadamia cultivars (Hawaiian cultivars: HAES 344, HAES 660, and HAES 816; Brazilian cultivars: IAC 9-20, IAC 4-12B, and IAC 4-20) or monocropped coffee (continuously cropped coffee monoculture) under drip irrigation and a mechanized system. Relative to the Brazilian cultivars, the smaller canopy diameters of the Hawaiian macadamia cultivars resulted in less competition with the intercropped coffee plants and required less pruning, enabling mechanized management of the crop. Annual pruning of the Brazilian cultivars resulted in lower kernel yields compared with the Hawaiian cultivar HAES 816, which exhibited the highest kernel yield. Regardless of the type of macadamia cultivar used, intercropping resulted in higher profits than monocropped coffee. We suggest that the Hawaiian cultivar HAES 816 is the most appropriate cultivar for irrigated intercropping with Arabica coffee and for maintaining the mechanization of cultural practices. This combination resulted in an economic benefit that was 178% greater than the benefits realized by monocropped coffee.